Art mind & brain: A cognitive approach to creativity - Gardner, Howard (New York Basic Books, 1982)
One of America's most brilliant cognitive psychologists offers some provocative answers to questions about the sources of human creativity."An outstanding brief reconnaissance of much of what is developing in the psychology of art."--Paul C. Vitz, "Contemporary Psychology"